On the simultaneous openness hypothesis: FDI, trade and TFP dynamics in Sub-Saharan Africa - Simplice Asongu; Joseph Nnanna; Paul N. Acha-Anyi (Journal of Economic Structures, 2020)
This study assesses the simultaneous openness hypothesis that trade modulates foreign direct investment (FDI) to induce positive net effects on total factor productivity (TFP) dynamics. Twenty-five countries in Sub-Saharan Africa and data for the period 1980 to 2014 are used. The empirical evidence is based on the Generalized Method of Moments. First, trade imports modulate FDI to overwhelmingly induce positive net effects on TFP, real TFP growth, welfare TFP and real welfare TFP. Second, with exceptions on TFP and welfare TFP where net effects are both positive and negative, trade exports modulate FDI to overwhelmingly induce positive net effects on real TFP growth and welfare real TFP. In summary, the tested hypothesis is valid for the most part. Policy implications are discussed.
Keywords: E23; F21; F30; L96; O55; 330; Productivity; Foreign investment; Sub-Saharan Africa